BUDIDAYA MICROGREEN UPAYA MENDUKUNG KETAHANAN PANGAN KELUARGA: STUDI KASUS DI TAMANTIRTO KASIHAN BANTUL - Aiman, Umul Aiman (FKIP Universitas Wisnuwardhana, 2023)
Microgreens are vegetables that are full of nutrition, healthy, free of pesticides and free of fertilizers. Microgreen comes from the word micro which means small and green means green, so it is a green plant that is harvested small, which is between 7 – 14 days from seedling depending on the type of plant. Microgreen cultivation does not require soil, fertilizers, or pesticides and is a difficult environment. Microgreen cultivation begins with selecting containers, and planting seeds in media (cocopeat, vermiculite, zeolite, rockwool, and sand).. Microgreens do not require direct sunlight, but you can use lamp light or artificial light, the required humidity is around 50% and the temperature is 24 – 29oC. The nutritional content in microgren includes alkaloids, chlorophyll, anthocyanins, and carotenoids. Community service is carried out in Tamantirto village which is a village in the Kasihan District, Bantul Regency. The culture of the Tamantirto people is not what it was 10 years ago with its rural characteristics, but now it has shifted into an urban area. What is striking is the shift in land use, especially the yard that is owned, no longer for growing crops but for residential/student boarding houses. With the limited land available, microgreen cultivation training is an alternative that is quite solutive and at the same time economically valuable, which can be implemented in Tamantirto village.